Comparison Of Growth Performance Through Different Levels Of Supplementary Feed In Fish Polyculture System - Sultana, Nazia; Jewel, Md Abu Sayed; Mondol, Md Rashedul Kabir (Journal of the Asiatic Society of Bangladesh, Science, 2016)
An experiment was carried out to evaluate the growth performance of carp polyculture system supplemented with different levels of supplementary feed. To undertake this investigation, two earthen ponds were stocked with 25% Labeo rohita, 25% Catla catla, 20% Labeo calbasu, 20% Ctenopharyngodon idella and 10% Hypopthalmichthys molitrix with a total stocking density of 10000/ha. The net fish production was found to be 2,166 and 3,874 kg/ha/yr in pond-01 and pond-02, respectively. The total cost of fish farming of pond-01 and pond-02 were 64,268 BDT and 88,568 BDT per ha. The total return of pond-01and pond-02 were BDT 1,04,280 BDT and 1,69,250 BDT per ha. Net benefit from pond-01 and pond-02 was 40,312 BDT and 80,682 BDT respectively. Net profit margin of pond-01 and pond-02 was 62.73% and 91.10%. And finally the benefit cost ratios (CBR) were found to be 0.62:1 and 0.91:1 in pond-01 and pond-02, respectively. Asiat. Soc. Bangladesh, Sci. 42(2): 229-234, December 2016